Organizational Commitment of Instructors of Private Colleges in Nueva Ecija - Santos, Angelo R. (International Journal of Humanities and Education Development (IJHED), 2020)
Organizational commitment is critical since high commitment rates contribute to several desirable organizational outcomes. It is important to promote organizational commitment among college instructors as they are committed to staying longer and performing better. The study described the personal commitment, service commitment, and career commitment of instructors from private colleges towards organizational commitment. This study used the descriptive method. The researcher distributed a survey questionnaire with likert-scale responses to a total of 83 instructors composed of 49 females and 39 males who were employed as instructor with a service length of not more than 2 years. Based on the findings of this research, it is then concluded, firstly, that the commitment towards organization of the instructors from private colleges can be shown into three different aspects personal, service, and career. Secondly, personal commitment towards organization is the most shown commitment of the instructors that they understand their contributions to the organization’s goals and their organizations inspire them to give their beat at work. Thirdly, in terms of service commitment towards organization, instructors from private colleges strongly agreed that their organization understands the needs of their customers for change thus they offer excellent customer service. Lastly, though resulted last in the aspects of commitment, career commitment towards organization proved that instructors from private colleges agreed that their career goals are important to their organizations. The researcher recommends that commitment towards organization must be taken into consideration of every person involved within it. Thus, not only for employees a commitment must be seen. Personal commitment is always an important aspect on how an employee will stay in an organization. However, the researcher recommends that an organization should also find other aspects of commitment towards organization aside from personal, service and career.